Elevated Serum Procalcitonin Levels in Chronic Kidney Diseases Patients Undergoing Renal Therapy - Farhan Ali Mazhar, Aisha Khalid, Ghulam Muhammad, Nida Basharat, Memona Imtiaz, Ahad Mehmood, Aiman Ijaz (Pakistan Journal of Medical & Health Sciences, 2022)
Introduction: Inflammation is an established mortality risk factor in chronic kidney disease patients and particularly in patients on dialysis. Objectives: The main objective of the study is to find the role of procalcitonin in chronic kidney diseases patients undergoing renal therapy. Material and methods: This cross sectional study was conducted Holy Family Hospital, Rawalpindi during November 2021 to June 2022. The data was collected with the permission of ethical committee of hospital. Baseline characteristics of patients were collected, including age, gender, BMI, history of diseases and time of dialysis. Results: The data was collected from 200 patients. There were 88 (44.0%) male and 112 (57.0%) female patients. The mean age for male was 45.9 ± 11.7 years and for female 49.8 ± 14.1 years. The PCT level in CKD patients (0.45 ± 0.70 ng/mL) was significantly higher as compared to reference value of healthy control subjects. Significance increase in the value of BUN, Na, K, CRP and BUN is also observed in CKD patients. Practical implication: PCT must be measured in CKD patients especially for dialysis patients. Conclusion: It is concluded that PCT levels were significantly high in CKD patients, thus PCT is a valuable marker for early diagnosis of CKD or patients undergoing HD. Keywords: CKD, PCT, CRP, Inflammation, Dialysis, Diagnosis